Gestion d’instance, proportionnalité et preuve civile : état provisoire des questions - Morissette, Yves-Marie (Les Cahiers de droit, 2009)
A major reform of civil procedure began in 2002 in the wake of the Ferland report, itself inspired by Lord Woolf’s report on civil justice in England and Wales. In both reports, the idea of proportionality is central, but the Civil Procedure Rules, which also address the issue of litigation costs, codified it much more vigorously than legislation adopted here. Local impact studies are also less probative than those conducted in England. Yet the overall assessment of these reforms leads to similar conclusions and ought to persuade the Quebec legislature to carry matters further in order to counteract the effects of a pervasive adversarial culture. To this end, closer case management, a tighter control on oral discovery and the use whenever possible of single, court-appointed or party-designated experts, are all desirable. Seen from this angle, the reform of 2002 in Quebec lags behind the reform based on the Woolf report.